Fundamental Movement Skills and Accelerometer-Measured Physical Activity Levels during Early Childhood: A Systematic Review - Alexandra Dobell; Andy Pringle; Mark A. Faghy; Clare M. P. Roscoe (MDPI AG, 2020)
Early childhood is a key period for children to begin developing and practicing fundamental movement skills (FMS), while aiming to perform sufficient physical activity (PA). This study reviews the current evidence for the levels of achievement in FMS and PA measured using accelerometers among 4-5-year-old children and examines differences by gender. This review was conducted using the PRISMA framework. Keyword searches were conducted in Pubmed, Medline, Google Scholar and SPORTDiscus. Inclusion criteria included age: 4-5 years old; FMS measurement: Test of Gross Motor Development 2 and 3; PA measurement: objective methods; balance measurement: static single limb; study design: cross-sectional observational/descriptive, randomised control trials, intervention studies; language: English. Twenty-eight articles from twenty-one countries met the inclusion criteria and were split into either FMS and PA articles (n = 10) or balance articles (n = 18). Three articles showed children achieving 60 min of moderate to vigorous PA per day, two articles demonstrated significant differences between girls' and boys' performance of locomotor skills and five reported locomotor skills to be more proficient than object control skills at this age for both genders. Balance was measured in time (n = 12), points score (n = 3) or biomechanical variables (n = 3), displaying heterogeneity of not only measurement but also outcomes within these data, with static single limb balance held between 6.67 to 87.6 s within the articles. Four articles reported girls to have better balance than boys. There is little conclusive evidence of the current levels for FMS, PA and balance achievement in young children 4-5 years of age. The academic literature consistently reports low levels of FMS competence and mixed evidence for PA levels. Inconsistencies lie in balance measurement methodology, with broad-ranging outcomes of both low and high achievement at 4-5 years old. Further research is required to focus on increasing practice opportunities for children to improve their FMS, increase PA levels and establish sufficient balance ability. Consistent and comparable outcomes during early childhood through more homogenous methodologies are warranted.